Evaluation and Investigation of Important Rheology Phenomena - Popalzai, Raihana (Journal of Natural Sciences – Kabul University, 2025)
Rheology is the study of the flow of matter, primarily in a liquid state, but also in "soft solids" or solids under conditions where they respond with plastic flow rather than deforming elastically in response to an applied force. Rheology is used to describe and assess the deformation and flow behavior of materials. Fluids flow at different speeds, and solids can be deformed to a certain extent. Substances such as oil, honey, shampoo, hand cream, toothpaste, sweet jelly, plastic materials, wood, and metals can be classified based on their physical behavior: liquids on one side, solids on the other, and highly viscous, semi-solid substances in between. This paper briefly presents the fundamental principles and basics of rheology.